THE REFLECTION OF ECONOMIC OPENNESS ON THE STRUCTURE OF THE BALANCE OF PAYMENTS - Abdullah, Karrar Naeem (Journal of Higher Education and Academic Advancement, 2024)
From the above, the researcher believes that it can be said that the third chapter reflects the reflection of economic openness on the structure of the balance of payments. The first section included an analysis of the items of the balance of payments in light of trade liberalization. The first requirement included the reflection of cash flows on the structure of the balance of payments in light of trade liberalization, indicating the effect of economic openness on the current account and the effect of economic openness on the capital account and external balance and imbalance. The balance of payments is affected by the movement of foreign trade at the level of economic analysis of any country, as it reflects the degree of overlap of the local economy with the global economy. In addition, the economic transactions included in it reflect, in terms of content, the structure of production and the strength of the national economy and its competitive ability. In the best case scenario, increased savings in the developing economy lead to an accumulation of non-tradable goods with a slight improvement in the balance of payments. As for investment in the developing economy, including government spending, it is likely to be less affected by profit expectations and interest rates than is usually the case in advanced capitalist economies. As a result, it is better to consider investment as a mere external variable, while the demand for exports is affected by factors such as The relationship between internal and external prices expressed in a common currency, the nature of trade restrictions in foreign markets, and the level of real income in the rest of the world. Most of these factors are independent of the level of income in the exporting country. Accordingly, the demand for exports can be considered an external variable. The main objective of banking supervision is to enhance the soundness of the banking system, so it requires that it be able to develop effectively. A good supervisory system requires a new and tight formulation of the legal framework related to supervision and supervisors obtaining sufficient resources and appropriate technology that enables them to obtain and review information. The second requirement: The correction mechanism in light of cash flows. Experimental evidence. The third requirement: The role of the central bank in processing cash flows. The role of the central bank in processing cash flows and the functions and objectives of banking supervision of the central bank.